2006
DOI: 10.1161/01.res.0000216288.93234.c3
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of Platelet-Derived Growth Factor Receptor-β by Oxidized Lipids in Vascular Cells and Atherosclerotic Lesions

Abstract: Abstract-The platelet-derived growth factor receptor-␤ (PDGFR␤) signaling pathway regulates smooth muscle cell (SMC) migration and proliferation and plays a role in the vascular wall response to injury. Oxidized low-density lipoprotein (oxLDL) in atherosclerotic lesions can activate the PDGFR␤ pathway, but the long-term effects of oxLDL on PDGFR␤ function are not well understood. We found that oxLDL induced a dual effect on PDGFR␤ signaling. Initial activation of the PDGFR was followed by desensitization of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 41 publications
3
63
0
2
Order By: Relevance
“…HNE can particularly form adducts with PDGFR (platelet-derived growth factor receptor) in atherosclerotic aortas and the use of the antioxidant hydralazine prevents HNE-related adduction and slows the progression of the disease. 38 HNE could also promote chronic inflammation by stimulating the expression and the synthesis of MCP-1 (monocyte chemotactic protein 1) and TGFb (transforming growth factor b) in macrophages and smooth muscle cells. 39 Moreover, HNE could affect the vascular cells' barrier integrity, leading to apoptosis of endothelial cells.…”
Section: Hne and Diseases Associated With Oxidative Damage: Links To mentioning
confidence: 99%
“…HNE can particularly form adducts with PDGFR (platelet-derived growth factor receptor) in atherosclerotic aortas and the use of the antioxidant hydralazine prevents HNE-related adduction and slows the progression of the disease. 38 HNE could also promote chronic inflammation by stimulating the expression and the synthesis of MCP-1 (monocyte chemotactic protein 1) and TGFb (transforming growth factor b) in macrophages and smooth muscle cells. 39 Moreover, HNE could affect the vascular cells' barrier integrity, leading to apoptosis of endothelial cells.…”
Section: Hne and Diseases Associated With Oxidative Damage: Links To mentioning
confidence: 99%
“…Desensitization of platelet derived growth factor receptor beta [27] In vitro and In vivo Inhibition of thioredoxin and thioredoxin reductase [28] Caco-2 human adenocarcinoma cells…”
Section: Biographiesmentioning
confidence: 99%
“…The activation of ERK1/2 was mediated by the activation of receptors for growth factors such as PDGFR-in SMCs 36,37) . We and other investigators showed that oxLDL stimulated the activation of PDGFR-in hCSMCs and rabbit arterial SMCs 15,38,39) . Our recent study further demonstrated that the production of MMP-1 induced by oxLDL and 4-HNE was suppressed under conditions where the activation of PDGFR-and ERK1/2 was inhibited by an inhibitor of tyrosine kinase (AG1295 and genistein) and by an inhibitor of mitogen-activated protein kinase/ERK kinase (PD98059), respectively 15) .…”
Section: Discussionmentioning
confidence: 52%
“…ox-LDL and 4-HNE have been shown to induce the activation of PDGFR-in hCSMCs and rabbit arterial SMCs 15,38,39) . We further reported that inhibition of the oxLDL-induced activation of PDGFR-resulted in the suppression of ERK1/2 phosphorylation and MMP-1 production 15) , suggesting that PDGFR-mediates the ERK1/2-dependent production of MMP-1 induced by oxLDL; therefore, the effects of Ginkgolon-24 on the activation of PDGFR-were examined.…”
Section: Effects Of Ginkgolon-24 On the Activation Of Pdgfr-mentioning
confidence: 98%